Doing Research at Online and Offline Intersections: Bringing Together Digital and Mobile Methodologies - Kaufmann, Katja (2022)
This thematic issue is an interdisciplinary exchange of methodological, practical, and ethical issues linked to conducting research across online and offline spaces in times of mobile technologies. It includes a wide range of disciplines, geographical locations, methodological approaches, and designs. The seven articles in this thematic issue are organized around three distinctive potential entry points: (a) researching across online and offline spaces with ethnographic, multisited, nonmedia-centric approaches; (b) making use of mobile media for researching across online and offline spaces; (c) researching emerging technologies built across online and offline spaces. All authors make their research processes transparent and share not only the methodical challenges and ethical dilemmas they faced, but also the opportunities that arose and methodological ways forward.